PROGNOSIS IN INCIDENT PARKINSONIAN COHORT: THE PINE STUDY. Issue 10 (9th September 2014) - Counsell, Carl; Fielding, Shona; Macleod, Angus; Forbes, Hazel; Harris, Clare
Abstract : Background: There are few prognostic data from community-based incident cohorts of people with Parkinson's disease (PD) or atypical parkinsonism. Methods: An incident cohort of people with degenerative or vascular parkinsonism and age-gender matched controls were followed up annually from diagnosis until death. Participants are seen yearly to gather data on multiple outcomes including survival, disability (dependency on others for activities of daily living) and institutionalisation. Research criteria are used to guide the clinical diagnosis. We analysed all-cause mortality, disability and institutionalisation by different diagnostic categories using survival analysis. Results: 361/377 (96%) incident patients (203 PD, 43 DLB, 43 Parkinson's plus, 39 vascular, 33 other; mean age at diagnosis 75 yrs) and 262 controls (mean age 75yrs) were followed up for a median of 5.5yrs. Mortality was higher in patients than controls (adjusted hazards ratio 2.01 for PD, 95% CI 1.30–3.12), especially for atypical parkinsonism (median survival PD 92 months, other disorders 25–39 months). At three years the rates of death or dependency were: controls 21%, PD 47%, atypical parkinsonism 95% whilst institutionalisation rates were: controls 2.5%, PD 7.5%, atypical parkinsonism 31–68%. Conclusion: Incident parkinsonian patients, particularly those with atypical parkinsonism, have significantly higher rates of death, dependency and institutionalisation than controls.